Teoría y evidencia sobre las políticas docentes en países desarrollados y en desarrollo - Emiliana Vegas; Alejandro Ganimian (Inter-American Development Bank (IDB), 2013)
– The past decade has seen the emergence of numerous rigorous impact evaluations of teacher policies. This paper reviews the economic theory and empirical evidence on eight teacher policy goals: (1) setting clear expectations for teachers; (2) attracting the best into teaching; (3) preparing teachers with useful training and experience; (4) matching teachers' skills with students' needs; (5) leading teachers with strong principals; (6) monitoring teaching and learning; (7) supporting teachers to improve instruction; and (8) motivating teachers to perform. The paper also discusses key concepts and methods in econometrics to understand existing studies and offers some directions for future research.
hdl:11319/4597
Keywords: I250; J450; I210; 330